The Pengaruh Penerapan Green Accounting dan Environmental Cost Terhadap Kinerja Keuangan pada Perusahaan Makanan dan Minuman - Nur’aini, Nur’aini; Permadi Karpriana, Angga; Noviarty, Helisa (Distribusi - Journal of Management and Business, 2024)
The purpose of this study is to determine whether green accounting and environmental costs affect the financial performance of food and beverage companies listed on the Indonesia Stock Exchange from 2021 to 2023. This research uses a purposive sampling technique, thus the secondary data utilized is based on specific criteria obtained from the annual reports and sustainability reports. A total of 66 samples (consisting of 22 companies) over three (3) years were used and analyzed using the Statistical Program for Social Science version 29 software. The data analysis employed includes descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The independent variables include green accounting, measured using the dummy variable PROPER, and environmental cost, measured by the allocation of funds for community development programs against profit. The dependent variable is financial performance, measured by return on assets. The results indicate that green accounting does not significantly affect financial performance, whereas environmental cost has a negative impact on financial performance.